2011
DOI: 10.1002/anie.201008102
|View full text |Cite
|
Sign up to set email alerts
|

Staudinger Ligation as a Method for Bioconjugation

Abstract: In 1919 the German chemist Hermann Staudinger was the first to describe the reaction between an azide and a phosphine. It was not until recently, however, that Bertozzi and co-workers recognized the potential of this reaction as a method for bioconjugation and transformed it into the so-called Staudinger ligation. The bio-orthogonal character of both the azide and the phosphine functions has resulted in the Staudinger ligation finding numerous applications in various complex biological systems. For example, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
147
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(149 citation statements)
references
References 156 publications
(162 reference statements)
2
147
0
Order By: Relevance
“…The [3 + 2] Huisgen cycloaddition and the copper catalyzed [3 + 2] Huisgen cycloaddition with dipolarophiles, the strained-promoted alkyne-azide cycloaddition (SPAAC) with strained alkynes and the Staudinger-Bertozzi ligation. 10,11 While the [3 + 2] Huisgen cycloaddition and its catalyzed version are not completely compatible with AuNPs chemistry because the high temperature or the Cu(I) required to push the reaction to completion cause severe nanoparticle aggregation, 12 the SPAAC reaction presents limited chemoselectivity due to the possibility of nucleophilic attacks (especially from thiols and amines largely present in biomolecules) to the highly reactive strained triple bond. [13][14][15] A recent work of ours highlighted this issue showing how post assembly deprotection of peptides once "clicked" on the AuNP surface was necessary to efficiently synthesize a nanoparticle bioconjugate through the SPAAC reaction.…”
mentioning
confidence: 99%
“…The [3 + 2] Huisgen cycloaddition and the copper catalyzed [3 + 2] Huisgen cycloaddition with dipolarophiles, the strained-promoted alkyne-azide cycloaddition (SPAAC) with strained alkynes and the Staudinger-Bertozzi ligation. 10,11 While the [3 + 2] Huisgen cycloaddition and its catalyzed version are not completely compatible with AuNPs chemistry because the high temperature or the Cu(I) required to push the reaction to completion cause severe nanoparticle aggregation, 12 the SPAAC reaction presents limited chemoselectivity due to the possibility of nucleophilic attacks (especially from thiols and amines largely present in biomolecules) to the highly reactive strained triple bond. [13][14][15] A recent work of ours highlighted this issue showing how post assembly deprotection of peptides once "clicked" on the AuNP surface was necessary to efficiently synthesize a nanoparticle bioconjugate through the SPAAC reaction.…”
mentioning
confidence: 99%
“…Independent on the variant of the Staudinger ligation (traceless or nontraceless), functionalized phosphanes act as starting material in general [6][7][8]. Furthermore, the traceless ligation can be divided in two approaches.…”
Section: Synthesis and X-ray Determinationmentioning
confidence: 99%
“…CONCLUSION X-ray structure determinations of the starting phosphanes and kinetic measurements of the reaction rate between fluorinated phosphane and various azides were accomplished under different reaction conditions to transfer and apply the traceless Staudinger ligation for future radiolabeling with short-lived β + -emitter fluorine-18 and other radionuclides. For this purpose, 19 F NMR was used due to the presence of 19 F in the starting material (phosphane 3) as well as in the corresponding products (7)(8)(9). The results of the measurements clearly indicate that it is possible to apply the traceless Staudinger ligation for radiolabeling purposes even in consideration of the short half-live of fluorine-18 under mild labeling conditions with a rather slow reaction rate.…”
Section: Determination Of K Obs Via 19 F Nmrmentioning
confidence: 99%
See 1 more Smart Citation
“…21 We have recently shown that the isonitrile group can also be used as a novel chemical reporter group for glycan metabolic labelling. 22 Azides incorporated in cell surface glycoproteins can be detected using either the Staudinger ligation, 23 the copper catalysed [3 + 2] cycloaddition with alkynes (with biologically compatible catalysts) 24 or the copper-free [3 + 2] cycloaddition with strained cyclooctynes. 25 Cyclopropenes and alkenes, on the other hand, can react with tetrazines.…”
Section: Introductionmentioning
confidence: 99%